Seismic response of braced excavation in sand - Wong, Desmond Jian How (2019)
The seismic response of multiple strut braced excavation in sand was investigated in this project. A series of numerical analyses was conducted using the numerical software, Plaxis 2D. Several design parameters such as wall stiffness, strut stiffness and acceleration amplitude were varied to study their impact on the dynamic analysis results. The lateral displacement, strut forces and wall bending moments at the end of earthquake motion were compared with the results yielded from static analysis. From the results, it was shown that the seismic load has a significant effect on braced excavation as it caused an increase in wall deflection and wall bending moment. Although the force in the lower struts were significantly affected by the earthquake, the loads in the top struts were relatively unaffected. Furthermore, it was found that while keeping the acceleration amplitude constant, the percentage increase in maximum wall bending moment was relatively independent from the variation in wall stiffness and strut stiffness. On the other hand, as acceleration amplitude increased, wall deflection, bending moment and strut forces increased significantly. Moreover, the apparent earth pressure behind the walls was also assessed in this study by backcalculating the strut forces measured from dynamic analysis. Overall, as acceleration amplitude increased, the apparent earth pressure exerted by the soil increased. It was shown that the earthquake caused an additional seismic force to act at the base of the retained soil. This was possibly due to the lack of restraint against wall movement at the bottom of the excavation, which caused the retained soil mass to surge into the excavation cavity near the formation level.